2023
DOI: 10.3390/vaccines11040855
|View full text |Cite
|
Sign up to set email alerts
|

BCG-Vaccinated Children with Contact to Tuberculosis Patients Show Delayed Conversion of Mycobacterium tuberculosis-Specific IFN-γ Release

Abstract: Mycobacterium (M.) bovis BCG vaccination is recommended for healthy babies after birth in several countries with a high prevalence of tuberculosis, including Ghana. Previous studies showed that BCG vaccination prevents individuals from developing severe clinical manifestations of tuberculosis, but BCG vaccination effects on the induction of IFN-γ after M. tuberculosis infection have hardly been investigated. Here, we performed IFN-γ-based T-cell assays (i.e., IFN-γ Release Assay, IGRA; T-cell activation and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Owusu et al's study suggested findings that the immune system's ability to recognize M. tuberculosis antigens happens earlier in kids and teens who haven't been vaccinated against BCG. This could be because of a higher threshold for T-cell activation or other factors that are important during early M. tuberculosis infections and delay T-cell conversion in people who have been vaccinated against BCG [36].…”
Section: Subbian Et Al 2020 [38]mentioning
confidence: 99%
“…Owusu et al's study suggested findings that the immune system's ability to recognize M. tuberculosis antigens happens earlier in kids and teens who haven't been vaccinated against BCG. This could be because of a higher threshold for T-cell activation or other factors that are important during early M. tuberculosis infections and delay T-cell conversion in people who have been vaccinated against BCG [36].…”
Section: Subbian Et Al 2020 [38]mentioning
confidence: 99%